Development of Low-Cost Natural Cooling Chamber for Preservation of Vegetables and Fruits in Rural Area - Kulkarni, Shubham; Haswal, Suraj; Galatage, Shrenik; Rankhambe, Sudhanshu; Ingale, Rupesh; Husainy, Avesahemad SN (Journal of Advanced Research in Mechanical Engineering and Technology, 2020)
India is an agricultural-based country and this output creates a deep impact on the Indian economy and the rest of the factors. Hence upgrading the traditional farming techniques by the use of technology should be our priority. In the case of fruits and Vegetable farming, it is seen that most of the output gets decomposed or gets dried after harvesting because of various problems like no preserving units into the farms, irregular timings of transportation facilities, wrong methods of storage, etc. This directly affects the fruits and vegetables by lowering the physiological loss in weight as well as by damaging their quality. So it is very important to find out a good preserving unit to increase the shelf life and to maintain the freshness of fruits and vegetables for a longer time. As well as, it is very difficult to install the refrigerating systems into the farms. It would cost a lot too. Hence we have to make this possible by the use of natural things which would be easily available to the farmers and very easy to build. These conditions can be achieved by installing a Natural cooling chamber. It provides higher humidity and lower temperature on the inner side of the chamber which would not promote any physiological loss in weight as well as other metabolic processes, resulting increase of shelf life by maintaining 10°C–15°C temperature below the ambient temperature. Also, it is very easy to build, has less maintenance, requires no electricity, and has a minimum cost of installation. Farmers would have a really good advantage of this natural preserver. How to cite this article: Kulkarni S, Haswal S, Galatage S et al. Development of Low-Cost Natural Cooling Chamber for Preservation of Vegetables and Fruits in Rural Area. J Adv Res Mech Engi Tech 2020; 7(3): 16-25. DOI: https://doi.org/10.24321/2454.8650.202005